PENGARUH TINGKAT PENDIDIKAN DAN PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGGANGGURAN INDONESIA - Yola Octavia; Fitri Ayu Ningrum; Desti Azaliah; Widia Sulastri; Reja Falentina Sababalat; Ansofino (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of workforce education levels and economic growth on the unemployment rate in Indonesia. The study uses Indonesian time series data from 1991–2024, with the unemployment rate as the dependent variable and education level and economic growth as independent variables, sourced from the World Bank. The analytical method used is multiple linear regression, preceded by a stationarity test to ensure the validity of the time series data. The results indicate that neither education level nor economic growth significantly influences the unemployment rate in Indonesia, indicating that changes in these two variables have not significantly reduced unemployment during the observation period. Simultaneously, the regression model is able to explain variations in the unemployment rate, but its contribution is limited, indicating that other factors outside the model are more dominant in determining national unemployment dynamics. These findings suggest the need for a more comprehensive employment policy, focusing not only on improving education and economic growth, but also on expanding job opportunities, improving the quality of the labor market, and equitable development across regions.